STABLE ISOTOPE FRACTIONATION OF SELENIUM BY NATURAL MICROBIAL CONSORTIA - Ellis A.S.; Johnson T.M.; Herbel M.J.; Bullen T.D. (My University, 2003)
The mobility and bioavailability of Se depend on its redox state, and reduction of Se oxyanions to less mobile, reduced species controls transport of this potentially toxic element in the environment. Stable isotope fractionation of Se is currently being developed as an indicator of Se immobilization through reduction. In this study, Se isotope fractionation resulting from reduction of Se(VI) and Se(IV) oxyanions by natural microbial consortia was measured in sediment slurry experiments under nearly natural conditions, with no substrate added. Experiments were conducted with a wide range of initial Se concentrations and with sediment and water from three locations with contrasting environmental settings. The products of Se(VI) and Se(IV) reduction were enriched in the lighter isotopes relative to the reactants. Shifts of -2.6%% to -3.1%% and -5.5%% to -5.7%%, respectively, were observed in the 80Se/76Se ratio. These isotopic fractionations did not depend significantly on initial Se concentrations, which were varied from 22 μg/l to 8 mg/l, or on geochemical differences among the sediments. These results provide estimates of Se isotope fractionation in organic-rich wetland environments but may not be appropriate for substrate-poor aquifers and marine sediments.
Keywords: SELENIUM; STABLE ISOTOPES; WATER CONTAMINATION; BACTERIA